EFEKTIVITAS TEKNIK SCAFFOLDING TERHADAP PEMBELAJARAN MENULIS TEKS DESKRIPSI KELAS V SDN 3 SUKAMANAH - Neneng Samrotul Fuadah; Dedi Heryadi; Winarti Dwi Febriani (LPPM Universitas Perjuangan Tasikmalaya, 2021)
Abstract: This research is motivated by the low understanding of students in describing objects, the low understanding of the use of punctuation points and commas and the lack of continuity of one sentence with another. In the Indonesian language learning process, various learning techniques are needed, therefore the Scaffolding learning technique is expected to give effectiveness to the learning outcomes of students. In general, the Scaffolding technique is used to involve students taking an active and independent role in doing the given task. The purpose of this research was carried out to describe the effectiveness of the Scaffolding technique in Indonesian language description learning and learning outcomes using the Scaffolding technique. The location of this research is SDN 3 Sukamanah, Cipedes District, Tasikmalaya City. The sampling technique used was saturated sampling. The data collection used was the observation sheet and the pretest and posttest question writing instruments descriptions. The results of this study are that the average pretest value is 51.76 and the average posttest score is 83.10. Based on the N-gain test using the One Sample T-Test produces a sig value. (2-tailed) of 0,000 in accordance with the sig value testing criteria. (2-tailed) <0.05, then Ha is accepted. The conclusion of this study is that there is a significant effectiveness of using Scaffolding techniques on the learning outcomes of writing descriptions in Indonesian.Keywords: Scaffolding; Learning; Description Text.Â Â Abstrak: Penelitian ini bertujuan untuk mengetahui efektivitas teknik Scaffolding pada pembelajaran menulis teks deskripsi dan prestasi belajar siswa. Pada umumnya teknik Scaffolding digunakan untuk melibatkan peserta didik perperan aktif dan mandiri dalam mengerjakan tugas yang diberikan. Tujuan dilaksanakan penelitian ini untuk mendeskripsikan keefektifan teknik Scaffolding pada pembelajaran deskripsi bahasa Indonesia dan hasil pembelajaran menggunakan teknik Scaffolding. Lokasi penelitian ini di SDN 3 Sukamanah Kecamatan Cipedes Kota Tasikmalaya. Teknik pengambilan sampel yang digunakan adalah sampling jenuh. Pengumpulan data yang digunakan adalah lembar observasi dan instrumen soal pretest dan posttest menulis deskripsi. Hasil penelitian ini adalah di dapat rata-rata nilai pretest 51,76 dan rata-rata nilai posttest 83,10. Berdasarkan uji N-gain menggunakan One Sampel T-Test menghasilkan nilai sig. (2-tailed) sebesar 0,000 sesuai dengan kriteria pengujian nilai sig. (2-tailed) < 0,05, maka Ha diterima. Kesimpulan penelitian ini adalah terdapat keefektifan yang signifikan penggunaan teknik Scaffolding pada hasil pembelajaran menulis deskripsi bahasa Indonesia.Kata Kunci: Scaffolding; Pembelajaran; Teks Deskripsi.